EFL Learners’ Self Efficacy and Its Relation to Reading Comprehension in Online Learning - Fatin Nadifa Tarigan; Siti Aminah Hasibuan; Lia Agustina Damanik; Rika Wahyuni Tambunan (Association of Language Teachers in Southeast Asia (ALTSA), 2022)
Self-efficacy plays an influential role in iniating any action including reading especially in online learning. Reading comprehension, along with all other language skills, has become a big concern in ELT, while self-efficacy is a pyschological aspect that affect the learners’ success in mastering the skill. In this regard, this study attempts to find out whether EFL learners’ self-efficacy affects the learners’ reading comprehension in Universitas Pembinaan Masyarakat Indonesia. The study applied correctional study with quantitative design. Participants in this study were 50 learners of English Education Department. A self-efficacy questionnaire (SEQ) and reading comprehension test were applied to the participants as parts of the correlational research model. The collected quantitative data were analyzed by Statistical Package for the Social Sciences (SPSS) program. The finding shows that the result of r-calculation for learners’ self-efficacy and their reading score is .765. The score of significance level is < 0.05 (0.000 < 0.05) which means that Ha was accepted and H0 was rejected. This score indicates that there is a positive correlation between the two variables.